2019
DOI: 10.3390/rs11182119
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Reflectance and Vegetation Indices for Unmanned Aerial Vehicle (UAV) Monitoring of Paddy Fields

Abstract: Reflectance and vegetation indices obtained from aerial images are often used for monitoring crop fields. In recent years, unmanned aerial vehicles (UAVs) have become popular and aerial images have been collected under various solar radiation conditions. The value of observed reflectance and vegetation indices are considered to be affected by solar radiation conditions, which may lead to inaccurate estimations of crop growth. In this study, in order to evaluate the effect of solar radiation conditions on aeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 24 publications
1
32
0
3
Order By: Relevance
“…In practice, vegetation index values do not remain fixed throughout the day, given that as solar altitude the angle of the sun above the horizon increases, vegetation index values are shown to decrease Cogliati et al, 2015;Rahman et al, 2015 . Furthermore, this effect is also influenced by the weather, with solar altitude affecting the vegetation index more on clear days when a greater proportion of the direct components of solar radiation reach lower altitudes and a smaller effect on cloudy days when the dispersion of sunlight components is greater Ishihara et al, 2015;Hashimoto et al, 2019 . In addition, vegetation density also has an effect, with areas of greater density being found to be affected to a lesser extent by solar altitude Ishihara et al, 2015 . The effect of sunlight conditions on the NDVI can be explained thus: the higher the solar altitude, the greater is the proportion of incoming light reaching the ground surface beneath the vegetation layer; under these circumstances, the ground has a greater influence on the reflected light being observed from above Ishihara et al, 2015 . The diffusion of incoming sunlight is greater on cloudy days, and the influence of sunlight conditions is reduced at higher vegetation densities. Moreover, these effects of sunlight conditions are apparent even when converting observational data to reflectance values.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, vegetation index values do not remain fixed throughout the day, given that as solar altitude the angle of the sun above the horizon increases, vegetation index values are shown to decrease Cogliati et al, 2015;Rahman et al, 2015 . Furthermore, this effect is also influenced by the weather, with solar altitude affecting the vegetation index more on clear days when a greater proportion of the direct components of solar radiation reach lower altitudes and a smaller effect on cloudy days when the dispersion of sunlight components is greater Ishihara et al, 2015;Hashimoto et al, 2019 . In addition, vegetation density also has an effect, with areas of greater density being found to be affected to a lesser extent by solar altitude Ishihara et al, 2015 . The effect of sunlight conditions on the NDVI can be explained thus: the higher the solar altitude, the greater is the proportion of incoming light reaching the ground surface beneath the vegetation layer; under these circumstances, the ground has a greater influence on the reflected light being observed from above Ishihara et al, 2015 . The diffusion of incoming sunlight is greater on cloudy days, and the influence of sunlight conditions is reduced at higher vegetation densities. Moreover, these effects of sunlight conditions are apparent even when converting observational data to reflectance values.…”
Section: Introductionmentioning
confidence: 99%
“…where NIR -near infrared reflection; Red -red reflection. As a result of simulations carried out by Japanese scientists, it is revealed that RVI (SR) is sensitive to solar radiation [17]. Its value is close to 1 if the object under study has the same reflection in both the Red and NIR channels, for example, soil.…”
Section: цифровые технологии Digital Technologiesmentioning
confidence: 99%
“…The digital processing of multispectral images acquired through UAV devices represents a useful tool to remotely observe the growth in riparian vegetation cover and, therefore, the hydrodynamic behavior of vegetated open channels colonized by riparian stands in natural phenological conditions. The first outcome of this research is represented by the direct correlation between NDVI derived by UAV-acquired multispectral images (NDVI UAV ) and LAI* measurements of the examined riparian vegetation cover, obtained by adopting the same methodology reported in previous precision agriculture studies on UAV-based crop production indicators [33][34][35]. Riparian vegetation NDVI UAV maps are extremely useful for flooding risk management in natural and urban vegetated areas.…”
Section: Arundo Donax Stands' Ndvi Mapmentioning
confidence: 99%